Juegos didácticos interactivos y su influencia en el proceso de aprendizaje de los estudiantes de 4to año de EGB de la Escuela 15 de Noviembre, Quevedo. 2023 - Andrade Chávez, Aura Mayling (2023)
Interactive educational games are strategies that awaken motivation and encourage learning in children through play, which, being a natural action, is frequently in their lives every day and helps them get the most out of it and use it, becoming a very useful resource. Valuable to learn. Healthy competition combined with challenges, rewards and social interaction turn out to be essential components in the effectiveness of these games in the learning process. Learning triggers a series of mental processes in students such as problem solving, critical thinking, decision making, planning and self-regulation of learning, which are fundamental for cognitive development, which is why this research work called Interactive didactic games and their influence on the learning process of 4th year EGB students at Escuela 15 de Noviembre, Quevedo, 2023 has the general objective of determining the influence of interactive educational games on the learning process of 4th year EGB students of the 15 de Noviembre Educational Unit, Quevedo, 2023. Due to the context of its development, it was based on qualitative research, through the bibliographic research technique and an incessant search for information in books, projects, theses, repositories and scientific articles to develop the two variables that support the theoretical framework, in addition as a research instrument the interview was used to collect relevant information and necessary based on the established objectives.